The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/elps.200800124
|View full text |Cite
|
Sign up to set email alerts
|

Improved conditions for fluorescent staining of proteins with 4,4′‐dianilino‐1,1′‐binaphthyl‐5,5′‐disulfonic acid in SDS‐PAGE

Abstract: A simple and sensitive fluorescent staining method for the detection of proteins in SDS-PAGE, namely IB (improved 4,4'-dianilino-1,1'-binaphthyl-5,5'-disulfonic acid) stain, is described. Non-covalent hydrophobic probe 4,4'-dianilino-1,1'-binaphthyl-5,5'-disulfonic acid was applied as a fluorescent dye, which can bind to hydrophobic sites in proteins non-specifically. As low as 1 ng of protein band can be detected briefly by 30 min washing followed by 15 min staining without the aiding of stop or destaining st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…It was reported that SR again yielded a LLD of 1-2 ng (SDS-6H marker proteins; Sigma) and a LDR of 2-500 ng [158]; little inter-protein variation was suggested by the LDR plot shown. Also, MALDI-ToF-MS analysis of standard proteins (BSA and CA) displayed sequence coverage between 29-34% and 48-58%, respectively (for protein loads between 4 and 64 ng) [157]. A comparison of this and the previous studies suggests that the LLD values are consistent.…”
Section: Non-reactive Fluorescent Dyessupporting
confidence: 68%
See 4 more Smart Citations
“…It was reported that SR again yielded a LLD of 1-2 ng (SDS-6H marker proteins; Sigma) and a LDR of 2-500 ng [158]; little inter-protein variation was suggested by the LDR plot shown. Also, MALDI-ToF-MS analysis of standard proteins (BSA and CA) displayed sequence coverage between 29-34% and 48-58%, respectively (for protein loads between 4 and 64 ng) [157]. A comparison of this and the previous studies suggests that the LLD values are consistent.…”
Section: Non-reactive Fluorescent Dyessupporting
confidence: 68%
“…Independent studies using the SR staining method detailed previously [20] were also carried out [157,158]. It was reported that SR again yielded a LLD of 1-2 ng (SDS-6H marker proteins; Sigma) and a LDR of 2-500 ng [158]; little inter-protein variation was suggested by the LDR plot shown.…”
Section: Non-reactive Fluorescent Dyesmentioning
confidence: 99%
See 3 more Smart Citations